Penerapan Metode Activity Based Costing System Dalam Menentukan Tarif Rawat Inap - Harmana, I Made Dwi (Journal of Public and Business Accounting, 2020)
Abstract. The purpose of this study was to determine the amount of inpatient rates when using the Activity Based Costing method at Abadi Medical Tabanan Hospital. As well as analyzing the large comparison of inpatient room rates between the Activity Based Costing System method and the traditional methods that have been implemented by the Abadi Medical Tabanan Hospital so far. This research is a descriptive study with a quantitative approach. The data collection techniques used in this study were documentation, observation, and interviews. The data analysis method used is by calculating the cost of inpatient services based on traditional cost accounting, calculating the cost of inpatient rooms based on the Activity Based Costing method, where the results of the calculation of the two methods will be compared to the cost of inpatient rooms. The results of the calculation of the cost of inpatient care at the Abadi Medical Tabanan Hospital using the Activity Based Costing System showed that the difference between the lower rates for VIP room 1 was IDR 31,997.07, while the higher rate occurred in VIP Room 2 with a difference of IDR 56,570. , 68, Class 1 IDR 193,765.10, Class 2 IDR 47,881.33 and class 3 IDR 79,375.90. Keywords: Activity Based Costing, traditional methods, inpatient rates